Pengaruh Pemberian Sari Ketela Ungu (Ipomea Batatas L.) Terhadap Kadar Insulin Tikus Wistar Bunting Model DMG - Ningrum Irfandi Putri, Nur Ilmya Nugraha; Mayangsari, Elly; Dewi, Mustika (Journal of Issues in Midwifery, 2023)
Background : Gestational Diabetes Mellitus is a complication of pregnancy in mothers without a previous diagnosis of diabetes, then chronic hyperglycemia is detected during pregnancy. Generally, this hyperglycemia is caused by impaired glucose tolerance due to pancreatic cell dysfunction, which begins with chronic insulin resistance conditions. The prevalence of GDM in Southeast Asia is 10%, while the overall diagnosis of diabetes in women in Indonesia is 1.8%. Nowadays, antioxidant therapy is being developed to treat DMG, one of which is the use of purple cassava plants.Objective : to determine the effect of purple cassava juice (Ipomea Batatas L.) on increasing insulin levels of wistar rats model of gestational diabetes mellitus. Methode : This study used an experimental method which was designed with the Post Test Only Group Design method. The total number of samples used in this study was 30 rats which were divided into 5 groups. Furthermore, the treatment group was given STZ injection of 45 mg/KgBB and then given purple cassava juice therapy for 14 days. Next, blood samples were tested for insulin levels using the ELISA Rat Kit. Result : There are no differences of insulin level between the treatment group and the control group because they had constant result. Conclusion : In this study, it was not found that there was an increase in insulin levels after treatment of purple yam juice for 14 days. So the research hypothesis was rejected. Keyword : Diabetes Mellitus Gestasional, Insulin Levels, Wistar Rats, Purple Yam Juice.